Magnetic stimulation of carotid sinus as a treatment for hypertension. Issue 2 (13th January 2019) - Li, Rongrong; Dai, Zhengze; Ye, Ruidong; Liu, Xinfeng; Xia, Zhengkun; Xu, Gelin
Abstract : Previously, we reported that magnetic stimulation of carotid sinus (MSCS) could lower arterial pressure in rabbits. In this randomized, sham‐controlled pilot study, we evaluated the effects of MSCS on blood pressure in pre‐hypertensive and hypertensive subjects. A total of 15 subjects with blood pressure higher than 130/80 mm Hg were randomized to receive sham or 1Hz MSCS. The changes of systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure (MAP) during treatment were compared between groups. The heart rate variability (HRV) and baroreflex sensitivity (BRS) before, during, and after treatments were analyzed. Reduction of SBP was significantly greater in subjects with MSCS than those with sham stimulation (6.6 ± 0.4 vs −2.5 ± 0.4 mm Hg, P  < 0.001). Reduction of DBP was significantly greater in subjects with MSCS than those with sham stimulation (1.2 ± 0.2 vs −2.8 ± 0.2 mm Hg, P  < 0.001). Reduction of MAP was significantly greater in subjects with MSCS than those with sham stimulation (1.4 ± 0.3 mm Hg vs −4.0 ± 0.3 mm Hg, P  < 0.001). Reduction of HR was significantly greater in subjects with MSCS than those with sham stimulation (0.5 ± 0.5 vs −1.9 ± 0.3 beats/min, P  = 0.002). BRS increased from 6.85 ± 0.77 to 8.79 ± 0.95 ms/mm Hg after MSCS compared with that at baseline ( P =  0.027). Thus, MSCS can lower blood pressure and heart rate in pre‐hypertensive and hypertensive subject, warranting further study for establishing MSCS as a treatment for hypertension.